16k+12h-1h+10k-3k=

Simple and best practice solution for 16k+12h-1h+10k-3k= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16k+12h-1h+10k-3k= equation:


Simplifying
16k + 12h + -1h + 10k + -3k = 0

Reorder the terms:
12h + -1h + 16k + 10k + -3k = 0

Combine like terms: 12h + -1h = 11h
11h + 16k + 10k + -3k = 0

Combine like terms: 16k + 10k = 26k
11h + 26k + -3k = 0

Combine like terms: 26k + -3k = 23k
11h + 23k = 0

Solving
11h + 23k = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-23k' to each side of the equation.
11h + 23k + -23k = 0 + -23k

Combine like terms: 23k + -23k = 0
11h + 0 = 0 + -23k
11h = 0 + -23k
Remove the zero:
11h = -23k

Divide each side by '11'.
h = -2.090909091k

Simplifying
h = -2.090909091k

See similar equations:

| 5(x+y)+3(y+1)= | | 6/10=12/x | | 16+1-16= | | 6-3s=-6 | | (2)x+15=3x+20 | | 15.36=y | | g(-x)=3x^2-2x+6 | | 22+6=180 | | 5x10^6/4x10^4 | | 3y+1-5(-3y-1)=2(y-3) | | 5x10^6/4x10^5 | | 18+7s=15.8 | | 9*x^2+4*y^2-24y=0 | | (5x+6)=(4x+11) | | -3x+12=3x | | (2)2x=6x-20 | | 2a-7=14a | | 3n+7-7n=34-12n+21 | | 24x^3-78x^2-24x= | | -19x+8=14 | | 30/144=1/x | | 2(x+y)+1x+6y= | | -6a-11=13 | | 7(x-5)-4=-3(-8x+9)-7x | | 7x-15y=-126 | | 360-3x/360 | | -44+r=-51 | | -7(w+1)=-3(8w-3)+7w | | 5v+x= | | 4z+8=38 | | 20x^2+224x-3840=0 | | ((4m^2)(3n^5))/((2m^-3)(-mn)^3) |

Equations solver categories